Classification of mucinous appendiceal neoplasm and pseudomyoxma peritonei (Journal of Pathology of Nepal, 2018)
Mucinous appendiceal tumors are uncommon and include a wide spectrum of tumors whose classification remained controversial. Some of these mucin producing appendiceal tumors can disseminate to the peritoneal cavity leading to pseudomyxoma peritonei (PMP). Despite several attempts to classify mucinous tumors of appendix and PMP by different authors in the past, no universally accepted classification system was present. The controversial issues were discussed at the 2012 World Congress of the Peritoneal Surface Oncology Group International (PSOGI) in Berlin. A panel of 71 experts from 13 different countries was formed under the lead co-ordinator Norman J. Carr. A total of 4 rounds of questionnaires and one meeting were held. The opinion of the majority was taken into account. Importance of intactness of muscularis mucosae, pushing invasion and infiltrative invasion were emphasized. The entities Low grade appendiceal mucinous neoplasm (LAMN) and High grade appendiceal mucinous neoplasm (HAMN) were defined.. The terminologies suggested for Goblet cell carcinoid and adenoneuroendocrine carcinoma were goblet cell tumor and adenocarcinoma ex goblet cell carcinoid. Acellular mucin in peritoneum was not classified under PMP which was classified into 3 categories depending upon low grade , high grade cytologic features and presence of signet ring cells. It was suggested to report the extent of mucin and cells separately. A reporting format solely for mucinous appendiceal tumors was formulated by the panel. However, there are some grey areas which may have to be addressed in future.